0884 Sleep as a Mediator between Chronic Stress and Metabolic Syndrome, the Coronary Artery Risk and Development in Young Adults (CARDIA) Study. (27th April 2018) - Johnson, D A; Knutson, K; Colangelo, L; Hale, L; Redline, S; Carnethon, M; Kershaw, K
Abstract: Introduction: Chronic exposure to stress is associated with metabolic syndrome, but the mechanism is unclear. We investigated sleep as a mediator between chronic stress and metabolic syndrome among CARDIA Study participants. Methods: Participants self-reported experiences of stressors (i.e., health problems, difficulties with job or ability to work, financial strain, relationship difficulties) for longer than 6 months to assess chronic stress at Year 15 examination. Wrist actigraphy-based sleep duration and sleep efficiency were measured for 6-days; sleep duration, sleep quality (PSQI) and daytime sleepiness (ESS) were self-reported at Year 20 examination. Metabolic syndrome was determined based on 3 out of 5 criteria for standardized sex-specific cut-offs for waist, triglycerides, blood pressure or hypertensive medications, and fasting glucose at Year 20 examination. Multivariable linear and logistic regression models were fit to determine the associations of chronic stress with sleep and metabolic syndrome, adjusting for demographics, socioeconomic status, and health behaviors. Mediation by sleep measures was assessed using the product of coefficients approach. Results: Among the study sample (N=606), the average age was 40 years (standard deviation (SD)=3.6), 58% were female, 52.6% had a college degree or higher, and 43% were black. Approximately 35% reported high chronic stress and 20.5% had metabolic syndrome. The average actigraphy-based sleep duration was 6.1 hours (SD=1.05) and 80% slept <7 hours. A high vs. low chronic stress score was associated with sleepiness (β=1.24, SE=0.39, P=0.002), a higher sleep efficiency score (β=2.00, SE=0.86, P=0.02), and a shorter self-reported sleep duration (β=-0.31, SE=0.12, P=0.008) but not sleep quality after adjusting for confounders. Also, high vs. low chronic stress was associated with a 1.86 higher odds (95% confidence interval: 1.12, 3.11) of metabolic syndrome after adjustment for confounders. Sleep measures were not associated with metabolic syndrome; thus, sleep did not mediate the chronic stress-metabolic syndrome relation. Conclusion: Chronic stress was associated with sleepiness, shorter self-reported sleep duration, higher sleep efficiency, and metabolic syndrome. Sleep did not appear to mediate the chronic stress-metabolic syndrome association. Support (If Any): NHLBI-K01HL138211.